Stranger in a strange land : an exploration of anti-LGBTQ structures in Singapore - Woo, Kai Shan (2016)
This paper utilizes Lizardo and Strand’s framework of refined cognitive approaches (toolkits and strong practices) to analyze the state of structural control in individuals and then the ways and reasons individuals act vis-à-vis these structures or lack thereof. Considering aforementioned documentation, it is safe to say the context of Singapore is one where stable socio-cognitive scaffoldings exist, at least regarding anti-LGBTQ sentiments and actors. The study focused on interactions and experiences were cognizant of, therefore identifying contexts where structures (especially practical institutions) are weak or opaque and correspondingly how structures from strong fields were used to justify individuals’ actions (discursive consciousness) and evoke the (re)production of strategically game-able fields (practical consciousness). Comparatives drawn showed heavy evidence of Foucaultian governmentality and Weberian instrumental rationality as reasoning interviewees gave for their actions.